Comparison of microvascular decompression and percutaneous balloon compression efficacy in patients with V2 idiopathic trigeminal neuralgia - Ji, Ye; Wang, Junwu (Frontiers in Neurology, 2024)
Objective: This study aims to compare the efficacy and long-term prognosis of microvascular decompression (MVD) versus percutaneous balloon compression (PBC) in patients with idiopathic V2 (maxillary branch) trigeminal neuralgia.We retrospectively analyzed the clinical information and follow-up data of patients who underwent surgical treatment for V2 idiopathic trigeminal neuralgia from January 2020 to January 2023. A total of 58 patients were included in the MVD group and 99 in the PBC group. All surgeries were performed by two physicians at the same center, with follow-up conducted by a separate, trained researcher. We compared the initial versus 12-month postoperative pain relief rates (scored using the BNI), surgical complications, and described pain relief rates after long-term follow-up in both groups using Kaplan-Meier analysis.The study included a total of 157 patients (MVD 58, PBC 99). The median age of patients in the MVD group was lower than that in the PBC group (58 [51-65] vs 63 [58-69], p=0.002). There was no significant difference between the two groups in terms of pain relief rates initially after surgery and at 12 months (p=0.521, p=0.713). However, the MVD group had significantly better outcomes regarding postoperative facial numbness (p<0.0001), masticatory weakness (p=0.0017), and other complications (p=0.04). Kaplan-Meier analysis showed that MVD provided a longer duration of pain relief than PBC (p=0.0323), with most recurrences in both groups occurring within 1-2 years after surgery.There were no significant differences in significant pain relief rates between the two groups initially after surgery and at 12 months. However, the MVD group showed a clear advantage over PBC regarding postoperative facial numbness, masticatory weakness, and other complications; moreover, Kaplan-Meier analysis revealed that MVD offers a longer duration of pain relief for patients.